Case-based research on democratization. Issue 1 (2nd January 2019) - Bogaards, Matthijs
ABSTRACT: Empirical research on democratization is dominated by case studies and small-N comparisons. This article is a first attempt to take stock of qualitative case-based research on democratization. It finds that most articles use methods implicitly rather than explicitly and are disconnected from the burgeoning literature on case-based methodology. This makes it difficult to summarize the substantive findings or to evaluate the contributions of the various approaches to our knowledge of democratic transition and consolidation. There is much to gain from a closer collaboration between methods experts and empirical researchers of democratization.